Adenosquamous cell carcinoma of the cervix — clinical and prognostic characteristics of the disease - E. K. Tanriverdieva; K. I. Zhordania; T. I. Zakharova; E. V. Prihodko; L. T. Mamedova (Опухоли женской репродуктивной системы, 2014)
Adenosquamous cell carcinoma of the cervix is a rare form of cancer of the cervix. Because of the small number of observations adenosquamous cell carcinoma of the cervix remains poorly understood disease, although the first mention of it dates back to 1956, when A. Glucksmann, and C.D. Cherry first described of mixed carcinoma (adenoacanthoma) of the uterine cervix.